Trace Metal Impurities Effects on the Formation of [64Cu]Cu-diacetyl-bis(N4-methylthiosemicarbazone) ([64Cu]Cu-ATSM) - Mitsuhiro Shinada; Hisashi Suzuki; Masayuki Hanyu; Chika Igarashi; Hiroki Matsumoto; Masashi Takahashi; Fukiko Hihara; Tomoko Tachibana; Chizuru Sogawa; Ming-Rong Zhang; Tatsuya Higashi; Hidemitsu Sato; et al. (Pharmaceuticals, 2023)
[64Cu]Cu-diacetyl-bis(N4-methylthiosemicarbazone) ([64Cu]Cu-ATSM) is a radioactive hypoxia-targeting therapeutic agent being investigated in clinical trials for malignant brain tumors. For the quality management of [64Cu]Cu-ATSM, understanding trace metal impurities’ effects on the chelate formation of 64Cu and ATSM is important. In this study, we conducted coordination chemistry studies on metal–ATSM complexes. First, the effects of nonradioactive metal ions (Cu2+, Ni2+, Zn2+, and Fe2+) on the formation of [64Cu]Cu-ATSM were evaluated. When the amount of Cu2+ or Ni2+ added was 1.2 mol or 288 mol, equivalent to ATSM, the labeling yield of [64Cu]Cu-ATSM fell below 90%. Little effect was observed even when excess amounts of Zn2+ or Fe2+ were added to the ATSM. Second, these metals were reacted with ATSM, and chelate formation was measured using ultraviolet–visible (UV-Vis) absorption spectra. UV-Vis spectra showed a rapid formation of Cu2+ and the ATSM complex upon mixing. The rate of chelate formation by Ni2+ and ATSM was lower than that by Cu-ATSM. Zn2+ and Fe2+ showed much slower reactions with the ATSM than Ni2+. Trace amounts of Ni2+, Zn2+, and Fe2+ showed little effect on [64Cu]Cu-ATSM’ quality, while the concentration of impurity Cu2+ must be controlled. These results can provide process management tools for radiopharmaceuticals.